Анализ показателей надежности компьютерной сети для различных вариантов управления потоками пакетов - Пустовойтов, Павел Евгеньевич; Круглов, Р. А.; Судаков, С. В. (НТУ "ХПИ", 2012)
В работе проанализирован состав суперпозиции потоков пакетов данных в компьютерной сети, показано, что управление приоритетами составляющих композиционного потока влияет на стохастические показатели системы обслуживания. В тестовой сети внедрен программный комплекс, который управляет потоками. Построены графики для общих показателей надежности компьютерной сети. It was researched the influence of package flow managing on reliability of network. It was built graphs of main indexes of reliabilities, using the developed program, which was tested in test network.

The results of experimental data of powder compositions state changes during electric discharge impact are given. The mechanisms of physical defects formation in matter during electric discharge impact with the purpose of powder bodies’ consolidation are proposed.
Keywords: прокси-сервер; узлы сети; скорость отклика; потери; reliability of network; ping; traffic; package loss